Peningkatan Penguasaan Kosakata Bahasa Jerman Melalui Media Kahoot - Nurming Saleh; Abdul Kasim Achmad; Nur Riswana Fauzia (Phonologie : Journal of Language and Literature, 2026)
Abstract. This study aims to determine the planning, process and process of language vocabulary German Students of class XI MIPA 6 MAN 1 Kota Makassar using Kahoot. This research is a classroom action study consistinng of two cycles. The subject of of this study is the class of XI MIPA 6 MAN 1 Kota Makassar which summarizes 38 students and a German teacher. This research data consists of two types of data. Qualitative data is obtained through the teacher's observation results that informed that the teacher can already use Kahoot well during the learning and the results of student observations that can inform students can choose vocabulary properly and well and make simple sentences in the use of German language. Quantitative data is obtained through a vocabulary test. The results showed that the German vocabulary test of the students in the cycle I 88.21 and cycle II 88.63. The results of this study indicate that the application of kahoot media can increase the management of the German vocabulary of the students of class XI MIPA 6 MAN 1 Kota MakassarKeyword:     Vocabulary Test, Improvement, Vocabulary, Kahoot, German Language